Plasma surgery and topical estriol: effects on the nasal mucosa and long-term results in patients with Osier's disease - Sadick, Haneen; Naim, Ramin; Oulmi-Kagermann, Jasmina; Hörmann, Karl; Bergler, Wolfgang (Otolaryngology - head and neck surgery, 2003)
OBJECTIVE: The study goal was to report on the long-term results and effect of argon plasma coagulation (APC) surgery and topical estriol in patients with Osier's disease who had recurrent epistaxis., STUDY DESIGN: In a prospective clinical study, 52 patients underwent APC and estriol application and were followed for 18 months regarding their bleeding frequency and intensity. Patient blood samples were obtained to determine the serum estriol levels. Scanning electron microscopy of the nasal mucosa enabled a better understanding concerning the effect of estriol on the nasal mucosa., RESULTS: Eighteen months after treatment, 96% of the patients stated a significantly reduced bleeding frequency and intensity. Under estriol influence, former berry-like telangiectasia of the nasal mucosa was flatter. The serum estriol levels did not increase significantly in any of the patients. No side effects from the use of topical estriol were observed., CONCLUSION: The combined treatment approach with APC and topical estriol significantly reduces epistaxis in Osier's disease., SIGNIFICANCE: APC and topical estriol have proved to be a promising alternative in the treatment of Osier's disease.